Studi Tentang Kesulitan Fokus Anak dalam Pembelajaran: Tinjauan Psikologis dan Edukatif - Sadiyah; Sista Liana; Mufaro’ah (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
The advancement of technology and the transformation of learning methods in the modern era have brought positive impacts to children's education. However, these developments also pose challenges, including increasingly complex focus difficulties among children. These focus difficulties affect children's academic, social, and emotional aspects. This study aims to identify the factors contributing to focus difficulties, encompassing psychological and educational aspects, and their impact on the learning process. From a psychological perspective, focus difficulties are often linked to emotional conditions such as anxiety and disorders like ADHD. Meanwhile, educational factors include teaching methods, curricula, and less conducive learning environments. This research employs a literature review method, with data collection conducted by searching, reading, analyzing, and citing relevant information from available literature. The data obtained is analyzed using a content analysis approach. This study highlights the importance of a holistic approach, both through psychological interventions and adjustments in teaching methods, to create a learning environment that supports children's focus abilities. The findings are expected to serve as a foundation for educators, parents, and psychologists in supporting children's optimal development through interactive and adaptive learning strategies.